Usual diet and dyslipidemia among workers assisted at a nutrition outpatient clinic in Bahia, Brazil (Research, Society and Development, 2025)
This study aims to assess the dietary patterns of workers using scores based on the frequency of consumption of both risk and protective foods for dyslipidemia, and to relate these patterns to total cholesterol and triglyceride levels. It is a cross-sectional study conducted with workers assisted at Bahia state's Reference Center for Occupational Health (CESAT). The workers underwent anthropometric assessments, and information was collected on their usual daily food intake during meals, with responses recorded in their medical charts for later classification. To assess the distribution of average levels of total cholesterol and triglycerides according to food consumption, two groups were formed: one consisting of foods considered to pose a risk for dyslipidemia, and another of low-risk (protective) foods. Based on these groups, two scores were created: Score I (score1 = Group 1/5) and Score II (score2 = Group 2/8), later categorized into tertiles. Data analysis was conducted using ANOVA, Spearman's rank correlation coefficient, and Multiple Linear Regression models. The results showed an increase in cholesterol and triglyceride levels proportional to the consumption of risk foods and a reduction in these levels only with the consumption of at least three protective foods. The study concludes that there is a need for a food education program that acknowledges the complexity of food choices and takes into account education level, access to food, housing and working conditions, as well as the individual's behavioral aspects in adopting healthy eating practices.